Novel internal measurements of ion cyclotron frequency range fast-ion driven modes. (5th January 2022) - Crocker, N.A.; Tang, S.X.; Thome, K.E.; Lestz, J.B.; Belova, E.V.; Zalzali, A.; Dendy, R.O.; Peebles, W.A.; Barada, K.K.; Hong, R.; Rhodes, T.L.; Wang, G.; et al.
Abstract: Novel internal measurements and analysis of ion cyclotron frequency range fast-ion driven modes in DIII-D are presented. Observations, including internal density fluctuation ( n ) measurements obtained via Doppler backscattering, are presented for modes at low harmonics of the ion cyclotron frequency localized in the edge. The measurements indicate that these waves, identified as coherent ion cyclotron emission (ICE), have high wave number, k ⊥ ρ fast ≳ 1, consistent with the cyclotron harmonic wave branch of the magnetoacoustic cyclotron instability, or electrostatic instability mechanisms. Measurements show extended spatial structure (at least ∼1/6 the minor radius). These edge ICE modes undergo amplitude modulation correlated with edge localized modes (ELM) that is qualitatively consistent with expectations for ELM-induced fast-ion transport.